The Role of Unplugged Activities in Developing Computational Thinking in Early Childhood: A Systematic Literature Review - Salistina, Dewi (Syntax Literate, 2026)
Computational thinking (CT) is a critical skill for young children, and its integration into early childhood education is essential for fostering problem-solving abilities. While digital tools have been widely used to teach CT, concerns about excessive screen time and unequal access to technology have raised challenges. Unplugged activities, which teach CT concepts without the use of digital devices, offer an alternative solution aligned with developmentally appropriate practices (DAP). This study aims to explore how unplugged activities support the development of CT in early childhood education, identifying effective strategies and their impact on young learners. A systematic literature review was conducted following the PRISMA guidelines. Articles were selected from databases such as Scopus, Web of Science, and ERIC. The review focused on empirical studies published between 2010 and 2024 that examined unplugged approaches to teaching CT to children aged 3–8 years. The study identified six key themes related to the development of CT through unplugged activities: decomposition, pattern recognition, abstraction, algorithm design, debugging, and knowledge transfer. Unplugged methods were found to promote tangible, hands-on experiences that align with children’s developmental stages, enhancing their understanding of computational concepts. The findings suggest that unplugged activities can effectively teach CT in early childhood settings, providing an accessible and engaging way to introduce computational concepts. This research has implications for curriculum developers, educators, and policymakers seeking to integrate CT into early childhood education in an equitable and developmentally appropriate manner.